Toxinological and pharmacological characterization of Southeast Asian Naja kaouthia (Monocled cobra) venom /Tan Kae Yi - Tan, Kae Yi (2016)
Snakebite envenomation is a neglected tropical disease and a serious public health problem in many countries in the tropics and subtropics, including Malaysia and Thailand. Antivenom remains as the only definitive treatment for snakebite envenomation; unfortunately, many nations do not have financial and technical resources to produce their own specific snake antivenom. These nations are relying on imported antivenoms that may not be very effective in treating envenomation by local snake species, due to geographical variations in the venom composition. These differences are medically relevant as they can lead to varied envenoming effects and treatment outcome. The monocled cobra (Naja kaouthia) is one of the most common dangerous species widely distributed in Indochina, northern Malayan Peninsula, northeastern India and southern China. The N. kaouthia venom from Thailand and Malaysia were previously shown to be substantially different in their median lethal doses (LD50); however, the differences in their venom compositions and pharmacological actions have not been elucidated. This present work profiled the venom proteomes of N. kaouthia from three different geographical regions, i.e. Malaysia (NK-M), Thailand (NK-T) and Vietnam (NK-V) using reverse-phase HPLC, SDS-PAGE and tandem mass spectrometry. The venom lethality and mechanism of neuromuscular blockade were also investigated in vivo using mice and in vitro using chick biventer cervicis nerve-muscle (CBCNM) preparation, while the neutralization of venom-induced toxic effects was assessed using Thai N. kaouthia Monovalent Antivenom (NKMAV) and/or Neuro Polyvalent Antivenom (NPAV) produced by Thai Red Cross Society. The venom proteome results revealed remarkable biogeographical variations in all three N. kaouthia venoms, with three-finger toxin (3FTx) being the most abundant but also the most varied among three venom samples studied. These venoms also exhibit differences in venom lethality and neuromuscular depressant activity that reflect the proteomic findings, with NK-T being the most lethal and most neurotoxic. Despite the variation in proteome, Thai-produced antivenoms were capable of neutralizing toxic effects of all three venoms with varying degree of effectiveness. The findings suggest that Thai-produced antivenoms could be used for the treatment of N. kaouthia bites in Malaysia and Vietnam. However, the recommended antivenom dosage may be tailored and further optimized. This present work also investigated the toxin-specific neutralization by NKMAV to understand why cobra antivenoms are generally of limited neutralization potency (< 2 mg/ml). The principal toxins of NK-T and Malaysian beaked sea snake (Hydrophis schistosus, HS-M) were purified and their neutralization by NKMAV and Australian CSL Sea Snake Antivenom (SSAV) were investigated. The neutralization profiles showed the low efficacy of antivenoms against low molecular mass toxins, particularly against the short neurotoxin (SNTX) of both venoms examined. This indicates that the limiting factor in neutralization potency is the poor ability of antivenoms to neutralize SNTX. Nevertheless, the SSAV was still substantially superior to NKMAV in neutralizing SNTX, presumably because the sea snake venom used as an immunogen in SSAV production contains a large amount of SNTX. The toxin-specific neutralization findings suggest that it is possible to improve the efficacy of cobra antivenom by increasing the amount of SNTX in the immunogen.